Differences in the long-term course of post-COVID-19 symptoms in adults and children across epidemic periods: A retrospective cohort study in Japan, 2020–2024 - Aya Sugiyama; Toshiro Takafuta; Kanon Abe; Yayoi Yoshinaga; Ko Ko; Tomoki Sato; Tomoyuki Akita; Masao Kuwabara; Shingo Fukuma; Junko Tanaka (PLoS ONE, 2026)
Background The prevalence of post-COVID-19 symptoms has been reported to decline since the Omicron variant became predominant. However, differences in their long-term course across epidemic periods and between adults and children, including recent Omicron sublineages, remain insufficiently understood. Methods We extended a previously reported retrospective cohort by conducting follow-up and an additional survey in Hiroshima, Japan. The study included 2,689 individuals diagnosed with COVID-19 between March 2020 and June 2024 (1,524 adults and 1,165 children). A self-administered questionnaire captured the presence and duration of 13 symptoms. Interval-censored survival analysis estimated prevalence over time, and proportional hazards models evaluated factors associated with symptom resolution. Results At six months, the estimated prevalence in adults was highest during the Delta period (47%) and lower during Omicron-2022 (23%) and Omicron-2024 (21%). In children, prevalence remained about one-quarter to one-third that of adults, with no notable differences between Omicron sublineages. At two years, persistent symptoms were reported by about 20% of adults infected before Omicron and 10% during Omicron periods, compared with 4.1% and 1.9% of children infected during the Delta and Omicron-2022 periods. Symptoms persisting beyond two years showed little further resolution, though in children they did not interfere with daily activities. In the Cox model, resolution was slower during the Delta period (HR 0.79) and faster during Omicron-2022 (HR 1.24) and Omicron-2024 (HR 1.30). Younger age, particularly ≤12 years, was strongly associated with faster recovery. Conclusion The long-term course of post-COVID-19 symptoms differed across epidemic periods and age groups. The risk was highest during Delta and lower among children and those infected during Omicron waves, yet some individuals experienced symptoms for over two years. Long-term follow-up and social support remain crucial to mitigate the burden of post-COVID-19 condition.